The impact of estrogen on benign breast tumors and exploration of recurrence mechanisms - Fan, Zhe; Wang, Huijin; Liu, Yu; Yu, Zongshuo; Li, Jingjing; Teng, Yuan (Frontiers in Oncology, 2025)
Benign breast tumors are among the most common breast diseases affecting women, with their pathogenesis closely linked to hormonal influences, particularly estrogen. This review offers a comprehensive overview of the mechanisms through which estrogen affects benign breast tumors and examines the role of estrogen in tumor cell growth, proliferation, and apoptosis. Furthermore, this review explores the recurrence mechanisms of benign breast tumors, analyzing factors such as hormone dependence, microenvironmental influences, and genetic susceptibility. By generating relevant literature, this article aims to offer new insights into clinical treatment and prevention strategies aimed at managing benign breast tumors.